Design and Development Fluxgate Magnetometer and Its Applications - Mitra Djamal (Institut Teknologi Bandung, 2006)
The paper explains design, development, and applications of fluxgate magnetometer, which is based on second harmonic Fourier component. The probe has a probe core of highly saturable material and at least two coils, a premagnetization coil and a pick-up coil. They are used to measure an external magnetic DC or low-frequency AC field, Bext. The probe is driven periodically into saturation by a sinusoidal current that flows through the premagnetization coil. It can be shown that the amplitude of the second harmonic frequency component will be measured by external magnetic field. The developed magnetometer can measure magnetic field with sensitivity 400mV/µT and relative error < 1.2 %. Some applications of the fluxgate magnetometer, e.g. non-contact current and displacement measurements have been developed and tested. It can be shown that the developed sensor can measure electric current until 1.9 A with relative error <5% and displacement in the range of 15 until 20 mm, with relative error <0.7%.